STRUCTURAL AND IMMUNOHISTOCHEMICAL FEATURES OF THE NORMAL BRAIN AND THEIR MODULATION BY EXTERNAL FACTORS. - Hamidova Guli Komilovna, (TADQIQOTLAR, 2025)
Abstract This article provides a scientific analysis of the normative morphological and immunohistochemical features of the brain, as well as the factors that influence them. The normal structure of brain tissue, the distinctive morphological characteristics of neurons and glial cells, the importance of the blood–brain barrier, and their role in overall  body  functioning  are  thoroughly  discussed.  The  article  also  examines  the possibilities  of  assessing  the  physiological  state  of  the  brain  using immunohistochemical methods that identify markers, proteins, and neurotransmitter systems. The influence of external and internal factors (genetic predisposition, toxic effects,  inflammatory  processes,  stress,  and  environmental  conditions)  on  brain morphology  and  immunohistochemical  indicators  is  analyzed  based  on  scientific literature. The results of this research serve as an important theoretical and practical foundation for the early diagnosis and prevention of neurological diseases, as well as for the development of neuroprotective therapies.